Consequences Of Long-Term Fertilization on Wetland Microbial Function - Koceja, Megan (East Carolina University, 2019)
Anthropogenic disturbances have led to increased deposition of nitrogen (N) and phosphorus (P) into soils. Nutrient enrichment of soils is known to increase plant biomass and also increase rates of microbial litter decomposition. Through decomposition, microorganisms release carbon (C) previously stored as organic C in soils into the atmosphere as carbon dioxide, a greenhouse gas. As these gaseous C emissions increase, global warming potential increases along with them. Understanding soil-microbe-plant interactions and their influence on decomposition rates is essential for understanding the causes of climate change and its mitigation. This study explores how shifts in organic C, N, and P caused by long-term nutrient enrichment and litter-type composition influence soil microbial function (e.g. decomposition). It is hypothesized that long-term nutrient enrichment causes shifts in soil microbial community structure that lead to higher rates of litter decomposition. Further, plant litter with a lower carbon C to N ratio (compared to high C:N ratio litter) is expected to decompose faster due to an available N source provided to nutrient-starved microbes. This study began at the long-term experimental fertilization and disturbance by mowing experiment at East Carolina University’s West Research Campus. In each of eight replicate mowed/fertilized and mowed/unfertilized plots, replicate bags of two different litter types (high C:N ratio rooibos tea and low C:N ratio green tea) were buried for 111 days. By using rooibos and green tea as a model plant litter with known C:N ratios, we are able to draw a link between litter type and decomposition rates by litter mass loss. Results revealed that soil microbes are capable of decomposing rooibos tea litter (higher C:N ratio) more quickly in fertilized compared to unfertilized. However, green tea litter (lower C:N ratio) decomposition rates were similar between fertilized and unfertilized plots. Overall, as predicted, the green tea litter decomposed faster than the rooibos tea litter. The outcomes of this study will provide insight into long-term effects of nutrient additions on soil microbial diversity and composition, related rates of decomposition, and the potential for climate change mitigation as nutrient enrichment continues to increase.
Keywords: decomposition; fertilization; microbial ecology; carbon cycling